Motor and Functional Abilities of U-19 Elite Croatian Soccer Players (Baltic Journal of Sport and Health Sciences, 2016)
Background. Soccer is known as one of the most popular games in the world. Because of constant profiling and improving, players and their conditioning abilities need to be on top level to achieve great sport results. The aim of this study was to determine conditioning profile of junior players playing on different playing positions. Methods. Sample of 85 junior elite soccer players (17.06 ± 0.74 years) was included in the study (height: 1.75 ± 0.05 m; weight: 73.59 ± 9.56 kg; body mass index: 23.97 ± 0.45 kg/cm 2 ). Sample of variables consisted of five motor ability tests (standing long jump-SLJ, high jump-HJ, 30 m sprint-SP30M, 60 m sprint-SP60M, 5 x 10 m sprint-SP5 x 10M) and one functional ability test (1500 m run-R1500M). To determine significant differences among players playing on different playing positions and to establish where those differences were, one-way ANOVA with Scheffe post-hoc  test  were  used.  For  better  understanding,  which  tests  distinguish  each  position  the  most,  discriminant analysis was performed. Results. Results showed that the sample which consisted of five groups (defenders, goalkeepers, attackers, stoppers and midfielders), significantly differed in variable SLJ (p = .00). Scheffe post-hoc test significant differences between defenders and goalkeepers (p = .01), goalkeepers and stoppers (p = .00) and goalkeepers and midfielders (p = .01). Conclusions. Results clearly represented homogenous collective, where players, no matter which position they were, had similar values in obtained tests. The explanation of obtained results could be found in similar preparedness and great sports form, which must be on optimal level for best performance.Keywords:  motor abilities, functional abilities, preparedness.